Integrasi Data Warehouse dan Sistem Informasi Geografis untuk Analisis Spasial Persebaran Mahasiswa Baru - Irmayani Irmayani; Rahman Rahman; Syahbudin Syahbudin; Asrul Azhari Muin; A. Mustika Abidin (Pusat Riset dan Inovasi Nasional, 2025)
Higher education institutions face challenges in managing large volumes of new student data, hindering strategic geographical distribution analysis. This research focuses on designing and building an integrated system utilizing a Data Warehouse and Geographic Information System (GIS) to analyze the distribution patterns of new students at UIN Alauddin Makassar. The system development uses the Waterfall model(I Putu Agus Eka Pratama, 2021), which includes structured stages from secondary data collection from the Academic Information System (SIAKAD), an ETL (Extract, Transform, Load) process into a Data Warehouse with a star schema architecture (Coronel & Morris, 2022), to spatial data visualization using GIS (Botha et al., 2023). The analysis of 15,826 student records from 2022-2024 reveals a high geographic concentration, with the top five regencies contributing 53.2% of all new students. The resulting web-based system provides an interactive thematic map that identifies regions with high applicant concentrations, offering strategic insights to support data-driven decision- making for university leadership (Corrin et al., 2023). This research demonstrates how the integration of Data Warehouse and GIS technology can optimize educational data governance and provide a solid foundation for strategic new student admission planning.